EFFORTS TO CONSERVE THE WEHOR WATER RESOURCES CHANGES AND CHALLENGES - Joseph Franky Leto Bere; Agustinus Bere; Adeo Dato Januario Barros Mbiri (Suluh Adiluhung Publisher (SAPub), 2024)
The issue of how the efforts to preserve the Wehor water resources carried out by indigenous peoples face environmental changes, as well as their challenges. The purpose of this study is to discuss the challenges of indigenous peoples in managing water resources. This study uses qualitative methods, data collection techniques through observation and interviews. The results of the study indicate the need for synergy and integration between regions, between sectors, between generations to anticipate the challenges of environmental change wisely and measurably.